1999
DOI: 10.1007/s004390050905
|View full text |Cite
|
Sign up to set email alerts
|

A trisomic germ cell line and precocious chromatid segregation leads to recurrent trisomy 21 conception

Abstract: A chromosomally normal 37-year-old woman was referred for preimplantation genetic diagnosis after having several conceptuses with trisomy 21. Segregation of chromosome 21 was assessed in unfertilised meiosis II oocytes and preimplantation embryos from PGD cycles using fluorescent in situ hybridisation (FISH). Of 7 preimplantation embryos, 5 were chromosomally abnormal with 4 having trisomy 21 and one being tetraploid. Of 4 oocytes, 3 had an abnormal chromosomal constitution with either an extra chromosome 21 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 25 publications
3
39
0
2
Order By: Relevance
“…Younger couples with three or more conceptions with the same trisomy are good candidates for gonadal mosaicism, as has been clearly demonstrated by several studies (Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004). Prospective studies on oocytes have also demonstrated that some women have a high risk of producing aneuploid oocytes.…”
Section: Predisposition To Aneuploidymentioning
confidence: 73%
See 1 more Smart Citation
“…Younger couples with three or more conceptions with the same trisomy are good candidates for gonadal mosaicism, as has been clearly demonstrated by several studies (Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004). Prospective studies on oocytes have also demonstrated that some women have a high risk of producing aneuploid oocytes.…”
Section: Predisposition To Aneuploidymentioning
confidence: 73%
“…Without further investigation it is not possible to determine whether this preexisting aneuploidy arose during the premeiotic divisions (germinal mosaicism) or if it was present initially in the embryonic gonad (gonadal mosaicism). Cytologically proven gonadal mosaicism was reported by Cozzi et al (1999) in a woman with three previous conceptions with trisomy 21 and for whom preimplantation diagnosis was performed. FISH analysis of unfertilised oocytes and corresponding 1 st PBs proved that gonadal mosaicism was the cause of the repeatedly abnormal conceptions.…”
Section: Studies On Mature Oocytesmentioning
confidence: 99%
“…These studies suggest that both, whole-chromosome nondisjunction as well as single-chromatid nondisjunction, contribute to the formation of numerical chromosomal abnormalities during first meiotic division (Munné et al, 1995Dailey et al, 1996;Verlinsky et al, 1996Verlinsky et al, , 1999Má rquez et al, 1998;Cozzi et al, 1999;Mahmood et al, 2000;Sandalinas et al, 2002). As reviewed by Pellestor et al (2003), many FISH studies have reported implausibly high rates of aneuploidy ranging from 37 to 44 % (Dailey et al, 1996;Dyban et al, 1996;Martini et al, 1997Martini et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…This premeiotic mechanism was found to be responsible for the presence of trisomic cells together with the euploid ones, when mature oocytes and embryos from euploid women were analysed. 11,12 Other authors have confirmed the existence of these premeiotic alterations as non-complementary results between 1PB-MII oocyte doublets in studies where the whole-chromosome complement was evaluated. Non-complementary rates between 1 and 15.5% have been described.…”
Section: Introductionmentioning
confidence: 90%